The invisible man [videorecording (DVD)] - Whannell, Leigh, 1977-; Whannell, Leigh, 1977-; Moss, Elisabeth, 1982-; Hodge, Aldis; Reid, Storm, 2003-; Wells, H. G. (Herbert George), 1866-1946 (Universal Pictures Home Entertainment, 2020)
When a woman's ex-husband commits suicide, a series of coincidences leads her to believe that his death was a hoax, and that she is being stalked by a man whom no one can see.